The Role of the Supramarginal Gyrus in Planning and Executing Tool Use - McDowell, Tomás (2019)
Tool use is an essential part of human day-to-day behaviour that permeates all cultures. Current neurocognitive models posit that tool use is reliant upon a left lateralised neural network, comprised of fronto-parietal circuits that separately mediate manipulation knowledge and visuomotor control. These functions must be integrated to allow effective tool grasping for functional use. The left supramarginal gyrus (SMG) has been posited as the point of integration between these cognitive functions as a well as a locus of stored representations of tool use gestures. Damage to the left inferior parietal lobule (encompassing the SMG) results in deficits in tool grasping and manipulation (observed in apraxia); and the SMG has shown preferential activation in response to tool related stimulus. Currently, the role of the SMG during tool action execution is controversial. Some studies have posited that left ventro-dorsal structures (inclusive of the SMG) are specified for manipulation knowledge for use of tools and are integral to generating action plans for grasp and use. Bilateral visuomotor action production systems execute the grasp plan based on visual-kinaesthetic feedback, independent of tool related input from the SMG. However, imaging data has highlighted bilateral SMG activation during tool grasp execution, while planning is associated with left lateralised SMG activation. Furthermore, the basis of tool cognition input is debated between two approaches; the manipulation based approach argues that tool cognition relies on stored representations of use, whereas the technical reasoning based approach argues a reliance on technical reasoning and knowledge of the mechanical principles of tools in relation to the user and targets for action. Both approaches posit an integral role of the SMG in this integrative process. The research questions of this thesis are threefold; (i) if the SMG is essential for planning, what function does it serve during execution of action? (ii) Are functionally salient elements of the grasp plan monitored during action execution and is this lateralised to the left SMG? (iii) What is the nature of conceptual input and tool cognition necessary for planning effective tool use? This thesis attempts to address these research questions through use of transcranial magnetic stimulation (TMS) and kinematic data analysis. In Chapter 1, evidence establishing current models of tool use and the SMG are discussed as well as the debate between manipulation and technical reasoning based approaches concerning the basis of cognition that facilitates tool use. In Chapter 2, a methodological study examines the accuracy of TMS coil placement across two methods of stereotaxic neuro-navigation, in preparation for the upcoming experiments. In Chapter 3, the role of the SMG during selection of functional grasp of tools for use is examined. An online correction task, in which tools were rotated rapidly during reaching (necessitating correction of grasp orientation) was conducted. This revealed a bilateral effect of SMG stimulation, resulting in delayed or erroneous grasp correction. This highlighted an integral role for the SMG in facilitating online correction of tool grasp for use. Contrary to current left lateralised models, results in this experiment are in line with a model of left SMG integration of tool grasp specific information, while the right SMG may be considered to support online correction without specific association with tool related input. However, this dissociation could not be confirmed without further control conditions. In Chapter 4, the aforementioned paradigm was expanded to include non-rotation controls and a control site of stimulation. In the previous paradigm, each trial required an online correction; this was discussed as a potential reason for right SMG stimulation effects. The right SMG has previously been associated with tasks requiring sustained attention and detection of changes in location or motion. Inclusion of non-rotation trials aimed to ensure the task focused on tool related input integrated with motion control, and limit participant anticipation of tool rotation. Findings demonstrated delays or erroneous grasp as a result of left SMG stimulation under certain rotation conditions, regardless of hand used. This implicates a role of the left SMG in providing dynamic reintegration of tool related input in response to changes in functional elements of the established grasp plan. Furthermore, the effects of right SMG stimulation were not present with the addition of non-rotation controls. In Chapter 5, a behavioural task was conducted to explore the nature of conceptual tool input necessary for selection of grasp; whether reliant on stored manipulation knowledge or technical reasoning (both thought to be mediated by the left SMG). Variances were examined in early movement kinematics dependent on familiarity with the tool, intention of action (transport or use) and affordance (varied orientation of the tool). This aimed to establish whether grasp actions were based on stored manipulation knowledge (which should be accessed faster for familiar tools and actions) or technical reasoning (regardless of familiarity, tools and actions should be constrained only by their structural and mechanical properties). Early movement kinematics indicated that actions were processed on the basis of structural properties and intention, as a function of affordance. While findings showed some support for the manipulation based approach, they more closely conform to the technical reasoning account. Developing this paradigm further, the experiment in Chapter 6 integrated TMS over the left anterior supramarginal gyrus (aSMG) during action planning. This aimed to assess the role of this region as the locus of integration of either manipulation knowledge or technical reasoning, into visuomotor systems for functional tool grasp. aSMG stimulation delayed selection of grasp orientation for use, but not transport, as a function of orientation of the tool. This implicates a role of the aSMG in supporting integration of technical reasoning into affordance processing structures. However, these findings do not discount the influence of stored gestures, or manipulation knowledge. This thesis has shown a dynamic role of the left SMG in selection of functional grasp of tools for use during action execution. This further shows that the left SMG monitors the conceptual fit between hand and tool as it pertains to the functional elements of the tool and position in relation to the user. The data indicates that this occurs when necessitated by changes to the tool orientation that affect functionally salient aspects of grasping. This is likely lateralised to the left hemisphere, however, the right SMG may serve functions such as sustained attention and location tracking that support online tool grasp selection, but are not reliant on tool related cognition. These findings support a basis in technical reasoning for selection of grasp when using familiar and novel tools, subject to constraints from the intention of action and affordances in the environment. However, these findings do not discount the role of manipulation or function knowledge for influencing online grasp selection. The methods developed in this thesis have revealed new avenues for research in the field of human tool use and could be further developed to continue exploration of this neural network.